1990
DOI: 10.1007/bf00000039
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative effects of allogeneic small-bowel transplantation of nutrient digestion and on body protein balance as determined in vivo in rats

Abstract: Heterotopic and orthotopic small-bowel allotransplantation was carried out in Wistar rats using grafts reduced to one-half of the original length. Portocaval venous anastomoses and intestinal end-to-end anastomoses were performed. Animals either with complete or with partially reduced native small-bowel served as control. In a total of 51 rats, 88 quantitative in vivo measurements of apparent digestion and absorption of dietary dry matter, organic matter, energy, protein, fat, total ash, and glucose were carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Therefore, knowledge of differences in susceptibility to cold preservation injury and subsequent reperfusion injury between the proximal and distal small bowel is important for avoiding primary mal-function. Many factors regarding intestinal function and enzymes have been reported as useful parameters for determining intestinal viability [4][5][6][7][8]. However, there is no single factor for distinguishing transplant tolerability between the jejunum and the ileum.…”
mentioning
confidence: 99%
“…Therefore, knowledge of differences in susceptibility to cold preservation injury and subsequent reperfusion injury between the proximal and distal small bowel is important for avoiding primary mal-function. Many factors regarding intestinal function and enzymes have been reported as useful parameters for determining intestinal viability [4][5][6][7][8]. However, there is no single factor for distinguishing transplant tolerability between the jejunum and the ileum.…”
mentioning
confidence: 99%
“…21 As it was not easy to obtain histological specimens after the stomas were closed, we assessed changes in the lipid absorption of the grafts. 11,12,20 Fecal fat excretion in the allo-R-SBT rats was significantly increased 14 days after the first grafting, when the grafts seemed to be normal in the H-SBT animals. Autopsy of the allo-R-SBT rats also confirmed no lymphocyte infiltration in the grafted intestine.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in the absorptive function of an ileal graft are considered to be a more useful parameter for the detection of chronic rejection than histological examination, as reported by us and others. [11][12][13] Histological changes in allo-intestinal grafts appear earlier after heterotopic than orthotopic transplantation. 14,15 Accordingly, we examined changes in fecal fat excretion after orthotopic segmental SBT in rats, comparing these findings with histological findings in heterotopic grafts.…”
Section: Discussionmentioning
confidence: 99%
“…They did not perform any histological investigation of the intestinal grafts though, while in our experiments all of the graft biopsies were normal. Kreuzer et al [16] have reported impaired fat and protein absorption of orthotopically transplanted halflength intestines in CyA-treated allografted rats. The impaired absorption was thought to be attributed to the short intestinal graft.…”
Section: Discussionmentioning
confidence: 99%